Artificial intelligence as a chance - Salmin, Leonid (project baikal, 2024)
The article analyses the influence of artificial intelligence technologies on the sphere of design and artistic culture in general, as well as on creative processes in design, architecture and visual arts. The factor of artificial intelligence is considered not so much in the applied and instrumental sense, but as a global driver of cultural and technological revolution, which can change the entire civilisational pattern of mankind in the foreseeable future. Under these conditions, the creative sphere becomes the “polygon of meanings” where strategic scenarios of human interaction with artificial intelligence can be worked out. The author investigates the socio-psychological and cultural aspects of readiness and unreadiness of creative professional culture for this mission.